2015
DOI: 10.1111/1744-9987.12327
|View full text |Cite
|
Sign up to set email alerts
|

Skin Perfusion Pressure and the Prevalence of Atherothrombosis in Hemodialysis Patients

Abstract: End-stage renal disease is associated with atherothrombosis (ATIS), which, in turn, can promote peripheral arterial occlusive disease (PAOD), coronary artery disease (CAD), and/or cerebrovascular disease (CVD). The aim of this study was to determine whether low plantar skin perfusion pressure (SPP) was related to ATIS among 122 patients receiving maintenance hemodialysis (HD) from March to November 2013 at our outpatient facility. We routinely measured SPP and used the value for analysis. In addition, we retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In recent years, the majority of research on SPP has been conducted using laser Doppler (7). In addition to its use in the diagnosis of critical limb ischemia (CLI) (20), in evaluating the severity of ischemia (21)(22)(23)(24), in the selection of the amputation plane (25), and in predicting wound healing, SPP is also used to evaluate the therapeutic efficacy of arterial revascularization surgery (26,27), endovascular therapy (28), and medicines used for the treatment of peripheral artery disease (PAD) and CLI (29,30). In a previous study, Watanabe et al (31) revised the laser Doppler technology, and SPP was measured using a thermostatic heating probe.…”
Section: Measurement Of Sppmentioning
confidence: 99%
“…In recent years, the majority of research on SPP has been conducted using laser Doppler (7). In addition to its use in the diagnosis of critical limb ischemia (CLI) (20), in evaluating the severity of ischemia (21)(22)(23)(24), in the selection of the amputation plane (25), and in predicting wound healing, SPP is also used to evaluate the therapeutic efficacy of arterial revascularization surgery (26,27), endovascular therapy (28), and medicines used for the treatment of peripheral artery disease (PAD) and CLI (29,30). In a previous study, Watanabe et al (31) revised the laser Doppler technology, and SPP was measured using a thermostatic heating probe.…”
Section: Measurement Of Sppmentioning
confidence: 99%
“…13,21,22) Since such diseases that cause thrombosis based on atherosclerosis show a common pathogenic pattern, a pathological concept called atherothrombosis (ATIS) has been proposed recently. 23,24) In addition, the presence of carotid artery plaque and intima-media thickness (IMT) of the carotid artery is recognized as surrogate markers of atherosclerosis, and CS has been reported to be often complicated by other atherosclerotic diseases. [25][26][27] Hertzer et al 12) performed CAG in 506 patients with extracranial CS and reported that the coronary artery was normal in only 7% and markedly stenosed in 35%.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated peripheral circulation by SPP which is a method measuring non-invasively dermal microcirculation by using Laser Doppler imaging-based methods because there are many reports describing them being useful to evaluate peripheral circulation disturbance such as lower limb ischemia in hemodialysis patients [7,8]. Evaluation of the SPP suggested that peripheral circulation was more stable during dialysis with NF (Fig.…”
Section: Discussionmentioning
confidence: 99%